2017
DOI: 10.3389/fpls.2017.01605
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Optimal Reference Genes for Expression Analysis in Radish (Raphanus sativus L.) and Its Relatives Based on Expression Stability

Abstract: Radish (Raphanus sativus) is an important cruciferous root crop with a close relationship to Chinese cabbage (Brassica rapa). RT-qPCR is used extensively to evaluate the expression levels of target genes, and accurate measurement of target gene expression with this method is determined by the valid reference genes used for data nomalization in different experimental conditions. Screening for appropriate reference genes with stable expression based on RT-qPCR data is important for gene expression and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 80 publications
(130 reference statements)
1
50
0
Order By: Relevance
“…Fortunately, BestKeeper still showed some conformance in the top five most stable reference genes with geNorm and Normfinder (Figure 4; Tables 2 and 3). Finally, a widely used web-based tool RefFinder was used to obtain a consensus stability ranking of each candidate gene under the given conditions according to the geometric mean of the attributed weights of each gene [45,47]. For RefFinder analysis, hnRNP, RPL5, TBP, and EF-1α were ranked as the top four most stable reference genes similar with the results from geNorm, Normfinder, and BestKeeper.…”
Section: Discussionmentioning
confidence: 77%
“…Fortunately, BestKeeper still showed some conformance in the top five most stable reference genes with geNorm and Normfinder (Figure 4; Tables 2 and 3). Finally, a widely used web-based tool RefFinder was used to obtain a consensus stability ranking of each candidate gene under the given conditions according to the geometric mean of the attributed weights of each gene [45,47]. For RefFinder analysis, hnRNP, RPL5, TBP, and EF-1α were ranked as the top four most stable reference genes similar with the results from geNorm, Normfinder, and BestKeeper.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, EF1-a gene was found to perform well for aphid-infested chrysanthemum 39 , and EF1A 2a, EF1A 1a1 and EF1A 2b were also identified as the best RG in JA-treated leaves of soybean 40 . GAPDH, ACTIN and UBC are the commonly used RGs for qRT-PCR analysis in varied plant, whose function is maintaining cell survival irrespective of physiological conditions [41][42][43] . In this study, we found that ACTIN, UBC and GAPDH were the top three appropriate RGs for the whole samples of T. aurantii-infested leaves ( Table 4), but GAPDH and ACTIN were less stable in peach 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Primers used for quantitative RT-PCR amplification of RNA2 were selected to anneal to corresponding identical sequences between CMV-Y and CMV-D8. ACTIN2/7 and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) genes [9] were used as reference genes for relative quantification (Additional file 5: Table S3).…”
Section: Relative Quantitative Reverse Transcription Polymerase Chainmentioning
confidence: 99%